The Effect Of HR Management And Career Development On Employee Performance With Job Satisfaction As An Intervening Variable In The Education Office And The Culture Of Padang Panjang City - Santi, Santi (Riset Sinergi Indonesia, 2024)
The Education and Culture Office of Padang Panjang City is a government agency responsible for all matters related to education in its area, tasked with carrying out government affairs in the field of education based on the principle of autonomy and assistance duties, and carrying out other tasks related to education. To improve service and employee satisfaction, agencies must have good management, which includes improved HR management and better career development programs. Effective HR management is needed in encouraging employee performance improvement but also needs to be supported by paying attention to employee job satisfaction. Therefore, the purpose of this study is to find out how the influence of HR management and career development on employee performance through job satisfaction as an intervening variable, the number of samples in this study was 41 respondents using the Smart PLS 3 analysis tool and data collection techniques in this study with the distribution of questionnaires using the Likert scale. The results of this study show that the most dominant variable, namely HR management, affects job satisfaction positively and significantly, if human resource management is done correctly, job satisfaction will also increase. In addition, job satisfaction has a positive and significant effect on employee performance, this shows that if employees feel happy and satisfied in carrying out their work, then employees can perform better. The most dominant indirect influence is that HR management has a positive and significant effect on employee performance through job satisfaction.